Camping, weather, and disasters: Extending the Construal Level Theory. (December 2021) - Craig, Christopher A.; Ma, Siyao; Karabas, Ismail; Feng, Song
Abstract: Camping is an outdoor accommodation and type of recreation that is susceptible to weather and climate change. Camping—in addition to the relationships camping shares with weather— remains understudied despite the subsectors' salient economic impact and high participation rate. The observable effects of non-meteorological/climatological (e.g., pandemic) is also a topic that has received limited attention. Accordingly, we introduce the Camping-Weather-Disaster (CWD) framework to examine the concurrent impact of weather and the COVID-19 disaster on post-disaster camping trip plans among leisure travelers in the 48 contiguous United States (n = 2442). Extending the Construal Level Theory, the CWD framework considers traveler construal (i.e., understanding) of a disaster and psychological distance (i.e., mental frame of reference) from a disaster alongside empirically observable state-level weather and COVID-19 cases. Results demonstrate that (1) concrete construal about timing and distance of travel is positively related to post-disaster camping trip plans; (2) weather is a significant predictor of post-disaster camping trip plans where there are regionally fewer COVID-19 cases; and (3) state-level COVID-19 cases are the most salient predictor of post-disaster camping trip plans where there are regionally more COVID-19 cases. Although the study context is camping, the CWD framework can be applied to other subsectors of tourism to build understanding and adaptive capacity to future natural conditions and disasters.